Sistem Informasi Pendataan Masyarakat Tidak Mampu Pada Kelurahan Binanga Mamuju Berbasis Website - Zulkifli Zulkifli; Musliadi KH; Ansar Ansar; Sumarlina Sumarlina; Najmawati Najmawati (LPPM - Universitas Universal, 2026)
The data collection process for underprivileged communities in Binanga Village, Mamuju Regency, was previously conducted conventionally using Microsoft Excel, Microsoft Word, and physical archives. This manual method was inefficient and highly susceptible to the loss of critical documents due to the absence of an integrated database system. This study aims to design and develop a web-based information system for underwriting underprivileged communities that can be accessed online from anywhere. The software development lifecycle (SDLC) employed is the Waterfall model, which encompasses the stages of requirements analysis, system design, implementation, and testing. The system was developed using Visual Studio Code as the source code editor, utilizing PHP, HTML, CSS, and JavaScript programming languages, alongside a MySQL database. The testing results demonstrate that the application operates in accordance with the initial design and functions optimally. The implementation of this information system significantly streamlines the data entry tasks for village officials while ensuring secure data storage within the system database.